Analisa Asam Salisilat Pada Perlengkapan Persedian Bermerk Bayi Di Pasar Blauran Surabaya - Nastiti Kartikorini (Universitas Muhammadiyah Surabaya, 2018)
Salicylic acid is a substance that is often added to skin care products for acne. In the regulation of the National Agency of Drug and Food Control No. Hk.03.1.23.08.11.07517 in 2011 concerning the technical requirements of cosmetics, salicylic acid levels are limited to 3% for rinse production and 2% for other production and are not used for children under 3 years. Using at high doses can cause the baby to bleed, mute and deaf. This is because the structure of the baby's skin is still thin, so it becomes susceptible to irritation and infection. The title of this research is Analysis of Salicylic Acid in the mains supplies barnded baby in the market blauran in Surabaya Region. The purpose identified salicylic acid content with qualitative tests on baby cosmetics circulating in Surabaya. The formulation of this problem is the presence or absence of Salicylic Acid in baby cosmetics. The type of research used descriptive, there were 26 baby cosmetics products in 4 types of products in the form of powder, soap, shampoo, and lotion which were conducted in the Laboratory of Muhammadiyah University of Surabaya in June 2018. Based on the results that found from 26 samples of baby cosmetics in the form of powder as much as 100% of soap, shampoo and lotions sold in Surabaya were not found for Salicylic Acid. So that all samples met the requirements based on the regulation of the National Agency of Drug and Food Control No.Hk.03.1.23.08.11.07517 in 2011 concerning the technical requirements of cosmetics materials, salicylic acid levels were limited to 3% not used for children under 3 years. Keywords: Baby supplies, Salicylic Acid